2000
DOI: 10.1152/jappl.2000.88.6.2045
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic markers of altered gait rhythm in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a disorder marked by loss of motoneurons. We hypothesized that subjects with ALS would have an altered gait rhythm, with an increase in both the magnitude of the stride-to-stride fluctuations and perturbations in the fluctuation dynamics. To test for this locomotor instability, we quantitatively compared the gait rhythm of subjects with ALS with that of normal controls and with that of subjects with Parkinson's disease (PD) and Huntington's disease (HD), pathologies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
341
1
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 415 publications
(362 citation statements)
references
References 36 publications
16
341
1
4
Order By: Relevance
“…Application of other analysis methods allows one to capture other features of gait time series and generate an array or matrix of outcome measures, each evaluating different aspects of the dynamics. Studies in neurodegenerative disease support the idea that such a matrix of dynamical measures may be helpful in more fully characterizing different pathologic states (Hausdorff, Cudkowicz, Firtion, Wei, & Goldberger, 1998;Hausdorff et al, 2000.…”
Section: Fractal-scaling and Additional Measures Of Gait Dynamicsmentioning
confidence: 94%
See 4 more Smart Citations
“…Application of other analysis methods allows one to capture other features of gait time series and generate an array or matrix of outcome measures, each evaluating different aspects of the dynamics. Studies in neurodegenerative disease support the idea that such a matrix of dynamical measures may be helpful in more fully characterizing different pathologic states (Hausdorff, Cudkowicz, Firtion, Wei, & Goldberger, 1998;Hausdorff et al, 2000.…”
Section: Fractal-scaling and Additional Measures Of Gait Dynamicsmentioning
confidence: 94%
“…In support of this idea, a recent study demonstrated that a pair of measures of gait dynamics that characterize the stride-tostride fluctuations can be used to distinguish among different neurodegenerative diseases (Carletti, Fanelli, & Guarino, 2006). In other words, by generating a matrix of parameters that reflect different features of gait dynamics, we may be able to improve our ability to evaluate gait dynamics and instability and its response to different therapeutic interventions (Hausdorff et al, 2000).…”
Section: Fractal-scaling and Additional Measures Of Gait Dynamicsmentioning
confidence: 95%
See 3 more Smart Citations